Compreendendo o gerenciamento do cuidado de enfermagem: dificuldades e estratégias sob a perspectiva de enfermeiros na assistência hospitalar. - Dayara Alves de Carvalho, Gyl (2016)
Introduction: Literature describes four inherent dimensions in nursing work, such as: care, education, management and knowledge production, existing a connection between management and care, which shaped the concept of care management so as to actualize it by satisfying the patient’s needs, as well as the needs of the team and of the health facility. Objectives: To analyze the comprehension of nurses about nursing care management at the hospital environment; to address the occurrence of articulation and divergences between managing activities and direct care; and, to build a theoretical model which represents the nurses’ experience concerning care management. Method: Exploratory-descriptive study, of qualitative approach, based on the Grounded Theory as theoretical and methodological benchmark. The population participating in this study was composed of 12 nurses from a teaching hospital placed in João Pessoa-Paraíba. Data collection was carried out by means of the application of a questionnaire and a semi-structured interview. At the end of the process, the analysis proceeded to the identification of the phenomena and of the central category of the study. Results: Based on data analysis, two phenomena, which composed the discussion, were identified: 1 – Comprehending Nursing Care Management; 2 – Experiencing difficulties when developing Nursing Care Management. Discussion: It was sought to describe the professionals’ experience and knowledge about the topic, pointing out the difficulties they find in the practice of care management, and the strategies used and proposed to overcome these limitations before the performance of an integral and qualified care. From the interaction of these two phenomena, a central category of the study emerged: Experiencing nursing care management and adopting strategies to overcome difficulties in its practice. Conclusion: The professionals’ reports demonstrate the acknowledgement of the importance of care management to qualify the assistance, even though they run into personal and organizational difficulties to develop it. They, therefore, corroborate the relevance of the Systematization of Nursing Assistance (SAE), of the technical and scientific knowledge and of the communication, associated with qualification of interpersonal relations in order to obtain the actual knowledge of the patients’ care and health needs, working as the basis for assistance planning and, consequently, for the practice of a proper management of care.